IMPROVING STUDENT’S VOCABULARY MASTERY THROUGH JIGSAW MODEL AT THE EIGHT GRADE STUDENTS’ OF SMP NEGERI 1 AMANDRAYA - Nurjeni Enjelika Buulolo (Research on English Language Education, 2024)
This research was aimed at improving students’ vocabulary mastery through jigsaw model. This research was designed by using Classroom Action Research (CAR) which was done in two cycles. The subject of this research was the Eight Grade students of SMP Negeri 1 Amandraya. They consist of 30 students. The instrument of collecting the data were observation paper and test. Based on the data analysis, the result of the researcher’s observation paper in cycle I for the first meeting was 79% and second meeting 86%. Cycle II for the first meeting 85% while in the second meeting was 93%. The result of student’s observation paper on the cycle I for the first meeting 70%, second meeting was 82% and cycle II in the first meeting 80% and the second meeting was 93%. Furthermore, the result of the test of students in cycle I, the average score 55, while cycle II was 82. Thus, it can be stated that the students problem in vocabulary mastery is solved by using jigsaw model. Finally, it is suggested to the English teacher to use jigsaw model to enrich the student vocabulary mastery.